Peran Sertifikasi Guru Terhadap Peningkatan Mutu Pembelajaran Dan Pengelolaan Kelas (Kajian Studi Literature Riview) - Muhammad Ihsan Dacholfany; Risnawati Risnawati; Megi Afroka; Rosa Zulfikhar; Lefina Souisa; Nasarudin Nasarudin (Journal on Education, 2023)
The purpose of this study is to determine the extent to which teacher certification plays a role in improving the quality of learning and classroom management. This research design is a literature study using a qualitative approach. This research describes the role of certified teachers synergizing with each other to carry out duties and responsibilities such as to carry out learning evaluations in formal education units consistently through daily test assessments, assignments, midterm and semester tests. Certification is a motivation for teachers to improve the quality of learning this is because teachers perform well in their fields. In line with that, teachers who have certification are also able to do good classroom management, because certified teachers are professional teachers in carrying out the learning process, so they are able to create a conducive, effective and comfortable classroom atmosphere. So that the teacher's job is not only to teach and educate, but also as a good classroom manager by acting as a facilitator, motivator, demonstrator, mediator and evaluator. All of this has been done well by certified teachers in applying discipline to manage learning and improve the quality of learning professionally in each.